Practice makes perfect French vocabulary building with suffixes and prefixes - Kurbegov, Eliane (New York Mcgraw-Hill Education, 2015)
Add 4,000 new French words to your vocabulary with frequently used word endings and beginnings; practice with more than 220 engaging exercises; and progress from beginner to advanced with a two-level approach.
Free flashcard practice app.
English and French.
Keywords: French language -- Vocabulary -- Problems, exercises, etc; French language -- Suffixes and prefixes; French language -- Textbooks for foreign speakers -- English